Densely Packed and Highly Ordered Carbon Flower Particles for High Volumetric Performance. Issue 7 (14th March 2021) - Gong, Huaxin; Chen, Shucheng; Ning, Rui; Chang, Ting-Hsiang; Tok, Jeffrey B.-H.; Bao, Zhenan
Abstract : Carbon materials with high specific surface areas are ideal support materials for many applications. However, high specific surface area and large pore volume usually render them with low bulk density, which is undesirable for applications aiming at high volumetric performance. Low bulk density stems from large interparticle‐free volume caused by inefficient random packing within the materials. Herein, a simple synthesis and assembly method is reported to afford dense carbon pellets with both high specific surface area and high bulk density, obtained from the ordered packing of low polydispersity carbon flower particles. The densely packed carbon flower particles exhibit similar specific surface area to their pressed powder analogs, while exhibiting a 66–84% increase in bulk density (0.815 g cm −3 ), and an ultrahigh volumetric surface area (1081 m 2 cm −3 ). The advantages of our materials are demonstrated by supercapacitors, which achieve a high volumetric capacitance of up to 153 F cm −3 . The results reinforce the importance of controlling particle size and shape for porous materials to reduce their bulk volume. The developed materials possessing high volumetric surface area will be useful for many applications, such as gas storage, supercapacitors, and batteries. Abstract : A strategy to synthesize high‐bulk‐density carbon materials by self‐assembling carbon flower particles into ordered arrays is reported. The densely packed carbon flowers demonstrated similar gravimetric surface areas to their powder analogs, while exhibiting up to 84% improvement in bulk density and a high volumetric surface area (1081 m 2 cm −3 ). These materials are promising for many energy storage related applications.